2022
DOI: 10.1177/10468781211073162
|View full text |Cite
|
Sign up to set email alerts
|

The Serious Game and Integrated Simulator for Cardiopulmonary Resuscitation Training in Nursing Students

Abstract: Background Nurses are often the first health professional who identify cardiopulmonary arrests in hospital settings; therefore, they require proficient cardiopulmonary resuscitation skills. Aim The purpose of this study was to evaluate game-based cardiopulmonary resuscitation training for first-year nursing students in terms of students’ knowledge levels, performance, satisfaction, and confidence. Methods This study was conducted following a quasi-experimental design. A total of 104 students were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
10
2
Order By: Relevance
“… In focus group interviews, students expressed their worries before the simulation and their satisfaction after the simulation. Demirtas et al., 2022 Turkey The purpose of this study was to evaluate game-based CPR training for first-year nursing students in terms of students’ knowledge levels, performance, satisfaction, and confidence. QE IG / IG Pre / post / post 104 First year CPR Serious Game & Integrated Real-Time Audiovisual Feedback Simulator / Real-time audiovisual feedback simulator Skill perf.…”
Section: Resultsmentioning
confidence: 99%
“… In focus group interviews, students expressed their worries before the simulation and their satisfaction after the simulation. Demirtas et al., 2022 Turkey The purpose of this study was to evaluate game-based CPR training for first-year nursing students in terms of students’ knowledge levels, performance, satisfaction, and confidence. QE IG / IG Pre / post / post 104 First year CPR Serious Game & Integrated Real-Time Audiovisual Feedback Simulator / Real-time audiovisual feedback simulator Skill perf.…”
Section: Resultsmentioning
confidence: 99%
“…In place of a specific medical radiation-specific framework, the INACSL (International Nursing Association of Clinical and Simulation Learning) Standards of Best Practice was adopted to inform proper use of simulation for participants (Watts et al 2021). This is based on Kolb’s Experiential Learning Theory, which has been used extensively to inform simulation-based education in healthcare fields (Demirtas et al 2022). Our approach therefore involved facilitating a learner-centered approach driven by the learning objectives and accompanying it with prebriefing and debriefing (Watts et al 2021).…”
Section: Research Protocolmentioning
confidence: 99%
“…To the best of our knowledge, only a limited number of studies have explored the use of serious smartphone games for teaching adult BLS to health care students [25][26][27][28][29]. Among these, only 1 study demonstrated an improvement in both the theoretical knowledge and practical skills associated with adult BLS [28]. Other studies have reported enhancements in either theoretical knowledge [29] or practical skills related to adult BLS.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported enhancements in either theoretical knowledge [29] or practical skills related to adult BLS. The positive effects of a serious smartphone game can be seen as early as 2 weeks [25,26], as well as 1 month after the intervention [27][28][29]. Studies have compared different teaching methods, where the use of serious smartphone games seems to have better results than simulation-based learning but is less effective than virtual reality-based game learning [26,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation